Complement Activation in Placental Malaria - McDonald, Chloe R.; Tran, Vanessa; Kain, Kevin C. (Frontiers in Microbiology, 2015)
Sixty percent of all pregnancies worldwide occur in malaria endemic regions. Pregnant women are at greater risk of malaria infection than their non-pregnant counterparts and are more likely to develop severe disease. Women with malaria infection in pregnancy have a higher risk of adverse birth outcomes including low birth weight resulting from intrauterine growth restriction and/or preterm birth. The complement system plays an essential role in placental and fetal development as well as the host innate immune response to malaria infection. Excessive or dysregulated complement activation has been associated with the pathobiology of severe malaria and with poor pregnancy outcomes, dependent and independent of infection. Here we review the role of complement in malaria and pregnancy and discuss its part in mediating altered placental angiogenesis, malaria-induced adverse birth outcomes, and disruptions to the in utero environment with possible consequences on fetal neurodevelopment. A detailed understanding of the mechanisms underlying adverse birth outcomes, and the impact of maternal malaria infection on fetal neurodevelopment, may lead to biomarkers to identify at risk pregnancies and novel therapeutic interventions to prevent the